2013
DOI: 10.1371/journal.pone.0071499
|View full text |Cite
|
Sign up to set email alerts
|

Diseases in Patients Coming to a Sleep Center with Symptoms Related to Restless Legs Syndrome

Abstract: Study ObjectiveTo explore the profile of patients who visit a sleep center with symptoms that fulfill the four essential criteria for restless legs syndrome (RLS).DesignA prospective study.SettingOutpatients from one sleep disorders clinic in Taiwan.Participants1,200 consecutive patients visit sleep disorders clinic with any sleep complaints.InterventionsAfter completing a history and physical examination, all participants answered the RLS questionnaire. Subjects who fulfilled the four essential criteria for R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…After controlling for key covariates, OSA was reported to be associated with 1.5 times higher odds of suicidal ideation and suicide planning in a secondary analysis of nationally representative US adults . Obstructive sleep apnea was reported to co-occur in 32% to 57.5% of individuals with RLS in previous studies, and treatment for OSA even benefited RLS symptoms in 20 of 26 patients . Nevertheless, research focusing on these sleep disorders and suicide in individuals with RLS is still scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After controlling for key covariates, OSA was reported to be associated with 1.5 times higher odds of suicidal ideation and suicide planning in a secondary analysis of nationally representative US adults . Obstructive sleep apnea was reported to co-occur in 32% to 57.5% of individuals with RLS in previous studies, and treatment for OSA even benefited RLS symptoms in 20 of 26 patients . Nevertheless, research focusing on these sleep disorders and suicide in individuals with RLS is still scarce.…”
Section: Discussionmentioning
confidence: 99%
“…For suicide or self-harm coding, the ICD-9 and International Classification of Diseases , Tenth Revision codes may yield different national statistics 50 and trends data, 51,52 although that coding transition did not alter the estimates of suicide-associated causes of death. 43,44,45,46 As mentioned before, because the ICD-9 codes were derived from claim documents, we may have underestimated the prevalence of suicide or self-harm without the inclusion of patients who did not seek care. Misclassification may occur if errors in ICD-9 coding were not randomly distributed among physicians, clinics, and hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to hypothesize that, being obesity more commonly also in patients with OSA, a considerable group of patients could suffer from both diseases, OSAS and RLS. However, there is no consensus on the prevalence of OSAS in patients with RLS [70,71]. Bianchi et al, have shown that among patients with RLS symptoms and no OSAS symptoms, the proportion of patients with elevated apnea-hypopnea index was more than 30%, suggesting the presence of occult OSAS in patients with RLS [72].…”
Section: Obesity and Restless-leg Syndromementioning
confidence: 99%
“…Studies on the pathogenesis of the disease have focused on iron metabolism, changes in dopaminergic system, hypoxic / inflammatory response and genetics [9,10]. It has been reported that RLS is more common in cases where peripheral oxygen saturation decreases, such as chronic obstructive pulmonary disease and obstructive sleep apnea [11,12] and improvement of RLS symptoms with correction of peripheral hypoxia [13]. Hypoxia in pathophysiology of RLS was supported with postmortem studies [14].…”
Section: Introductionmentioning
confidence: 97%